Catalyzed Radical Termination in the Presence of Tellanyl Radicals. Issue 56 (12th September 2017) - Ribelli, Thomas G.; Rahaman, S. M. Wahidur; Matyjaszewski, Krzysztof; Poli, Rinaldo
Abstract: The decomposition of the diazo initiator dimethyl 2, 2′‐azobis(isobutyrate) (V‐601), generating the Me2 C . (CO2 Me) radical, affords essentially the same fraction of disproportionation and combination in media with a large range of viscosity (C6 D6, [D6 ]DMSO, and PEG 200) in the 25–100 °C range. This is in stark contrast to recent results by Yamago et al. on the same radical generated from Me2 C(TeMe)(CO2 Me) and on other X‐TeR systems (X=polymer chain or unimer model; R=Me, Ph). The discrepancy is rationalized on the basis of an unprecedented RTe . ‐catalyzed radical disproportionation, with support from DFT calculations and photochemicaL V‐601 decomposition in the presence of Te2 Ph2 . Abstract : The bimolecular termination of (CH3 )2 C . CO2 CH3 radicals generated from V‐601 is essentially solvent‐ and temperature independent, contrary to that of the same radicals generated from (CH3 )2 C(TeMe)CO2 CH3 ; DFT calculations and V‐601 photolysis in the presence of Te2 Ph2 suggest an unprecedented Te‐catalyzed disproportionation to account for these different results (see figure).